Human Complexity: The Final Frontier - Harry Francis Mallgrave (Oz, 2014)
We often take it for granted that architecture is a visual art. We think of it in visual terms. We design and evaluate our producton visually… But do we experience a building or an urban environment exclusively in visual terms?